Impact of Stepwise Climate-smart cocoa practices on beneficiary farmers-under CCAFS project in Ghana (Project endline) - Dalaa, Mustapha Alasan; Saeed, Abdul-Razak; Deffor, Eric Worlanyo; Kofituo, Rich Kofi; Asare, Richard (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2021)
This report is an end-line study report of the International Institute of Tropical Agriculture (IITA) project titled “Climate Smart Cocoa and its influence on voluntary standards and Impact lending in West Africa”. The project in Ghana focused on introducing cocoa farmers to Climate-Smart Agriculture (CSA) practices using a “stepwise approach” which is termed “Stepwise Climate Smart Cocoa practices”. The study sought to ascertain the level of acceptance and adoption of the stepwise climate-smart cocoa (CSC) practices within the project implementation areas in Ghana. Analysis of data from 1113 project targeted farmers using descriptive statistics and regression analysis showed that adoption of CSC practices is very high among farmers (Over 98% of farmers are aware and carrying out CSC practices) because of the project pieces of training and 99% of farmers stated that CSC practices are beneficial. The majority of farmers (53%) who were directly trained on stepwise CSC practices went on to train colleague farmers who were not part of the project partners’ Farmer Business Organization. The factors that influenced the adoption of stepwise CSC practices are the age of the farmer, level of education of the farmer, cocoa farming experience, household size, walking distance to the farm, and land size. The majority of farmers are willing to pay for CSC practices at a cost ranging from GHS 100.00 to GHS 480.00. Few farmers (3%) expressed having challenges with the adoption of CSC, relating this to financial difficulties with affording practices, tiredness in carrying out practices, the time-consuming nature of carrying out practices, and the fear of adoption.